ANALISA PERANCANGAN SISTEM INVENTORY GUNA PENINGKATAN PRODUKTIVITAS KERJA - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2010)
In line with growth of era requirement of speed and of accuracy (information accuracy) represent vital matter in information era these days. In a company represent a system, representing network a work from procedures which is interaction, flock together to activity or to finish a certain target. System Planning and control of Production is system which effort manufacture used to plan goods to produce pursuant to order of customer. This goods production require matured planning in preparation of material required, to be sent out for to supplier. Because, delay of ordering will influence production process and too much kept material will influence stock holding cost. Keywords: Speed and accuracy of information, system design analysis